POSTURAL REGULATION OF PATIENTS IN THE ACUTE PERIOD OF ISCHEMIC STROKE ACCORDING TO STABILOMETER DATA - Коновалова, Нина Геннадьевна; Шарапова, Ирина Николаевна; Горохова, Лариса Геннадьевна; Ромашевская, Нелли Ивановна; Макарова, Лариса Николаевна (Medicine in Kuzbass, 2021)
13 patients in the acute period of ischemic stroke where examined.Objective – to analyze the features of patients’ in acute period of ischemic strokepostural regulation.Methods. Romberg's tests on a computer stabilograph with analysis of indicators: the area and the length of the statokinesiogram; the ratio of the length to the area; speed of the common center of pressure’smovement; displacement of the general center of pressure; root-mean-square deviation of the center of pressure; 60 % of spectrum in frontal and sagittal planes; Romberg coefficient.Results. The area of the patients’ statokinesiogram exceeded the norm by almost 2 times, the values of the center of pressure’s standard deviation in the frontal and sagittal planes were increased, the speed of center’s of pressure movement was lower than that in healthy people.The center of pressure in sagittal plane is displaced forward, the displacement in the frontal plane did not exceed the norm. Closing eyes led to increasing the statokinesiogram’s area. Romberg's coefficient averaged 309, that is higher than in healthy people standing. The asymmetry of the posture in frontal plane increased, the center of pressure shifted forward. The speed of common center of pressure’smigration, the frequency of oscillations in the sagittal and frontal planes increased.Conclusions. The stabilogram of patients in the acute period of stroke has the following features: length, area, standard deviationsare greater than that of healthy people. The speed of general center of pressure’s movement is lower; the vibration spectrum is shifted to the low frequency band. Closing the eyes leads to increasing in the length, area of the statokinesiogram, more than when healthy personsstanding. There was no clear displacement of the general center of pressure in the frontal plane when patients stood with their eyes open. Vision deprivation leads to a shift in the center of pressure in the frontal plane.
Keywords: ischemic stroke; stabilogram; postural regulation